PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KEMAMPUAN GERAK DASAR GULING DEPAN DALAM SENAM LANTAI - SYAMSUL HUDA, MUCHAMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the conventional learning process, most of the material submitted by teachers were not completely understand by the students. This is  because there is no feedback between the material provided by the teacher and a student. It brings a bad result to the unmaximal student’s ability. Students will have under value of the KKM and percentage of students who no success more than 80%. It Seen from the initial assessment has been carried out on the material before forward rolling motion gymnastics floor, there are 12 students or 46.15% gain  criterion of "less" and 14 students received a score of 70 to the top or 53.85% got the criteria of "moderate" and "good". So the researchers will use a type STAD cooperative learning model in this study, because the researcher as the novice teachers and the other benefits in this model  is that students can also  play an active role both  students who able to todo and the unable. The purpose of this study is to determine the improvement of psychomotor skills of students in forward rolling movement by using the model of student teams learning achievement division (STAD). The study, conducted by researchers is action research within the scope of the classroom action research (PTK). Subjects of the study were fifth grade students Creative Schools 16 Surabaya Muhammadiyah elementary school. This is because all of the problems that show in this class. The results are as follows: In cycle 1, the number of students who succeeded beyond KKM as many as 21 students. While the percentage is 81.41%. Because the percentage of students who successfully more than 80%, then it can be said that the results of the application type STAD cooperative learning model to improve the forward rolling is completed at the first cycle. Then increase the forward rolling test results of students learning before and after receiving cooperative learning model type that is  27.56% of  STAD. Keywords: Classroom Action Research (PTK), Cooperative Learning Model Type STAD, Forward rolling, Elementary School